2015
DOI: 10.5688/ajpe7910155
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional Peer Teaching of Pharmacy and Physical Therapy Students

Abstract: Objective. To evaluate an interprofessional peer-teaching activity during which physical therapy students instructed undergraduate pharmacy students on 3 ambulatory devices (canes, crutches, walkers). Design. The pre/post evaluation of 2 pharmacy undergraduate classes included 220 students, 110 per year. After pharmacy students completed a 10-point, knowledge-based pretest, they participated in a hands-on activity with physical therapy students teaching them about sizing, use, and safety of canes, crutches, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…Sadowski et al. () indicated that “While there may be some concern that faculty members have greater knowledge or expertise, and therefore, would do a superior job of transferring information, the social and cognitive congruence of a peer teacher compensates for this” (p. 5). Cognitive congruence focuses on the ability of an instructor and student to share the same language (Cate and Durning ; Yu et al.…”
Section: Theoretical Justificationmentioning
confidence: 99%
See 4 more Smart Citations
“…Sadowski et al. () indicated that “While there may be some concern that faculty members have greater knowledge or expertise, and therefore, would do a superior job of transferring information, the social and cognitive congruence of a peer teacher compensates for this” (p. 5). Cognitive congruence focuses on the ability of an instructor and student to share the same language (Cate and Durning ; Yu et al.…”
Section: Theoretical Justificationmentioning
confidence: 99%
“…Students who served as peer teachers reported increased confidence regarding in their intellectual abilities (Sadowski et al. ; Sarquis et al. ).…”
Section: Impact Of Engaging Students In Teachingmentioning
confidence: 99%
See 3 more Smart Citations